2012
DOI: 10.1100/2012/541786
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mechanisms and Function Prediction of Long Noncoding RNA

Abstract: The central dogma of gene expression considers RNA as the carrier of genetic information from DNA to protein. However, it has become more and more clear that RNA plays more important roles than simply being the information carrier. Recently, whole genome transcriptomic analyses have identified large numbers of dynamically expressed long noncoding RNAs (lncRNAs), many of which are involved in a variety of biological functions. Even so, the functions and molecular mechanisms of most lncRNAs still remain elusive.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
101
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(103 citation statements)
references
References 112 publications
1
101
0
1
Order By: Relevance
“…With the advance of high resolution microarray and genome wide sequencing technology, lncRNAs have recently caught increasing attention ( Ma et al, 2012;Tang et al, 2013;Liu et al, 2014). Some studies suggest that dysexpression of lncRNAs is associated with numerous diseases including cancer (Wapinski and Chang, 2011;Tang et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…With the advance of high resolution microarray and genome wide sequencing technology, lncRNAs have recently caught increasing attention ( Ma et al, 2012;Tang et al, 2013;Liu et al, 2014). Some studies suggest that dysexpression of lncRNAs is associated with numerous diseases including cancer (Wapinski and Chang, 2011;Tang et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Once an altered lncRNA has been identified, the next challenge is to elucidate its biological role, as exemplified by the relatively small number of lncRNAs with well-characterized function. 16 As in vitro experiments that screen for oncogenic function are labor intensive and time consuming to conduct for numerous lncRNAs, previous studies have used guilt-by-association methods to associate a lncRNA in a pathway or biological process based on the known function of highly co-expressed protein coding genes. 1,[16][17][18] When applied across large patient cohorts, this represents an effective option for systematically predicting lncRNA function to guide subsequent functional experiments.…”
Section: Introductionmentioning
confidence: 99%
“…16 As in vitro experiments that screen for oncogenic function are labor intensive and time consuming to conduct for numerous lncRNAs, previous studies have used guilt-by-association methods to associate a lncRNA in a pathway or biological process based on the known function of highly co-expressed protein coding genes. 1,[16][17][18] When applied across large patient cohorts, this represents an effective option for systematically predicting lncRNA function to guide subsequent functional experiments. Additionally, we identified altered lncRNAs that may be up-or down-regulated due to an amplification or deletion, respectively, and associated lncRNA expression with the mutational status of commonly mutated genes in cancer which could suggest an acquired functional role in tumors.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have indicated that the abnormal expression of certain well-defined lncRNAs, including HOX transcript antisense RNA, maternally expressed 3 and metastasis associated lung adenocarcinoma transcript 1, are strongly correlated with CRC development and progression (23)(24)(25). Therefore, the role of lncRNAs in the development and progression of CRC is gaining increasing attention (26).…”
Section: Discussionmentioning
confidence: 99%